Corporate strategy and firm performance in finance industry: the moderating role risk management committee - Kallamu, Basiru Salisu; Mohd Saat, Nur Ashikin; Senik, Rosmila (Management Journals, 2013)
Although there are a lot of studies on corporate strategy and performance, very little research has been carried out on particular industry in a developing country such as Malaysia. Moreover, the studies examined direct impact of strategy on firm performance. Using a sample of thirty seven listed finance firms in Malaysia, we test the moderating effect of separate risk management committee (RMC) on the relationship between corporate strategy and firm performance. Based on agency theory, the study hypothesized that separate RMC moderates the relationship between corporate strategy and firm performance. The result indicates that the presence of a RMC significantly moderate the relationship between non-traditional strategy and firm performance in a positive direction. Our result provide empirical support for agency theory which suggests that presence of subcommittee of the board of directors helps to facilitate the effective monitoring of management thereby reducing the risk taking activities of managers which will enhance firm performance.